Effective Strategies in Teaching Moral Creeds to Increase Faith and Moral Goodness in MTs Alkhairaat Pelawa Students - Zahrah; Yuliani; Triwahyuni, Yuyun; Kurniawati, Yuyun (Jurnal Profesi Guru Indonesia, 2024)
Aqidah Akhlak learning has a crucial role in shaping the character and faith of students, especially at the Madrasah Tsanawiyah (MTs) level. Education that focuses on strengthening Islamic values ​​is expected to form a generation that is not only academically intelligent, but also has high morality. This article examines effective strategies in teaching Aqidah Akhlak to improve faith and shape noble morals for MTs Alkhairaat Pelawa students. This study uses a qualitative descriptive method with observation, interview, and documentation techniques to explore the learning strategies applied by educators. The results of the study indicate that effective strategies in teaching Aqidah Akhlak include a contextual approach that links the material to everyday life, an exemplary method that emphasizes the importance of real examples from teachers, experience-based learning so that students better understand and internalize the values ​​taught, and the use of technology as an interactive learning medium. In addition, a conducive madrasah environment and full support from teachers and parents are supporting factors in the success of this learning. By implementing the right strategy, increasing students' faith and moral quality can be achieved optimally, so that they are able to practice Islamic values ​​in their daily lives.